حكامة تسيير الجماعات الإقليمية في الجزائر - حسان, حضري (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
يعد إرساء آليات الحكامة المحلية من أهم الحلول المطروحة لتجاوز سوء تسيير وتنظيم الجماعات الإقليمية وسط تضخم معدلات الفساد الإداري وضعف مردودية المجالس المنتخبة، وهو ما يستدعي استحضار مجموعة من الدعامات قصد تفعيل الحكامة الجيدة وفق منظور إصلاحي جديد قائم على ترسيخ معايير المشاركة والشفافية والمساءلة في التسيير بغرض تحسين أداء الهيئات المحلية، مع إعادة ترتيب الأدوار والمسؤوليات بينها وبين الدولة والقطاع الخاص ومنظمات المجتمع المدني من أجل تحقيق التنمية الشاملة وتطوير الخدمات المحلية. إنّ الانتقال إلى الحكامة الجيدة في تسيير الجماعات الإقليمية في الجزائر يظل رهين تفعيل الآليات والميكانزمات التنظيمية والوظيفية التي تهم تسيير مجالها الإداري والمالي وتتجاوز الاختلالات والعراقيل التي مافتئ يعكسها الواقع المعاش، لذلك أصبح من الضروري تحسين طرق تسيير البلدية والولاية كجماعات إقليمية وفاعل رئيسي في تسيير الشأن المحلي في إطار الحكامة المحلية من خلال التحيين المستمر للنصوص القانونية قصد تطوير نظام اللامركزية وتوسيع نطاق مشاركة المواطن رفقة المجتمع المدني في اتخاذ القرار المحلي وتنفيذه ومتابعته في إطار الشفافية، مع تفعيل الحكامة الإدارية بأخلقة وعصرنة التسيير الإداري للجماعات الإقليمية، وكذا الحكامة المالية بعقلنة تسييرها المالي وتطوير مواردها الذاتية وتفعيل أداء الرقابة المالية. The establishment of local governance mechanisms is one of the most important solutions proposed to overcome the mismanagement and organization of local authorities Amidst the inflated levels of administrative corruption and the weak efficiency of the elected councils, which necessitates bringing in a set of pillars in order to activate good governance according to a new reform perspective based on establishing standards of participation, transparency and accountability in management in order to improve the performance of local bodies, while rearranging roles and responsibilities between them and the state and the sector private and civil society organizations in order to achieve comprehensive development and develop local services. The transition to good governance in the management of local authorities in Algeria remains dependent on the activation of the organizational and functional mechanisms and mechanisms that concern the management of its administrative and financial sphere and overcome the imbalances and obstacles that have always been reflected in the lived reality, therefore it has become necessary to improve the management methods of the municipality and the state as local authorities and a major actor in the conduct of local affairs in the framework of local governance through the continuous updating of legal texts in order to develop the decentralization system and expand the scope of citizen participation, along with civil society, in local decision-making, implementation and follow-up within the framework of transparency, with activating administrative governance by moralizing and modernizing the administrative management of local authorities, as well as financial governance by rationalizing its financial management, developing its own resources and activating the performance of financial control.
أطروحة دكتوراه تخصص قانون جماعات محلية في الحقوق و العلوم السياسية
Keywords: الجماعات الإقليمية، الحكامة المحلية، التسيير المحلي، أخلقة الإدارة المحلية، الحكامة المالية، الحكامة الإدارية; local authorities, local governance, local management, ethics of local administration, financial governance, administrative governance.